STRATEGI PENGEMBANGAN PARIWISATA DI WILAYAH PROVINSI KALIMANTAN TENGAH PANDEMI COVID-19 - Brian Christabel Tobias; Try Willy Kristianto; Wijoko Lertariono (Jurusan Ilmu Pemerintahan, 2021)
Tourism has an important role in the country's economic growth, by contributing to job creation, production activities and national income, private sector growth and infrastructure development. Tourism in Central Kalimantan has its own charm for domestic and foreign tourists. It is indeed a priority to bring in many tourists, there are approximately 352 tourist attractions that are excellent. But at the beginning of 2020, when the world was shaken by the presence of the Covid-19 outbreak, the Indonesian government acted through strategic policies to suppress the spread of Covid-19 in the public. Therefore, the central government implemented a policy of implementing large-scale social restrictions (PSBB) until there was a lock down policy in several regions including Central Kalimantan Province. Prevention and Control of Covid-19 which limits people from doing activities outside the home to minimize the spread of Covid-19 including limiting and even delaying tourist activities that have a negative impact on the economy in the tourism sector. Through this paper, we provide strategic recommendations that are relevant to tourism in Central Kalimantan Province, namely the development of tourist markets, development of tourism imagery, development of tourism marketing partnerships, and development of tourism promotions to optimize tourism development during the COVID-19 pandemic.